2023
DOI: 10.1097/qai.0000000000003133
|View full text |Cite
|
Sign up to set email alerts
|

Recent Alcohol Use Is Associated With Increased Pre-exposure Prophylaxis (PrEP) Continuation and Adherence Among Pregnant and Postpartum Women in South Africa

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…An illustrative example comes from a South African study involving pregnant and post-partum women where 1 in 3 women reported hazardous alcohol use. At 3 months, 58% of women were reportedly still using PrEP and alcohol use correlated with higher odds of PrEP continuation (aOR 1.54, 95% CI 1.16-2.06) [40]. In our study, while there was a higher inclination towards initiating PrEP among the high-risk alcohol group, continuation rates remained largely uniform irrespective of alcohol use.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…An illustrative example comes from a South African study involving pregnant and post-partum women where 1 in 3 women reported hazardous alcohol use. At 3 months, 58% of women were reportedly still using PrEP and alcohol use correlated with higher odds of PrEP continuation (aOR 1.54, 95% CI 1.16-2.06) [40]. In our study, while there was a higher inclination towards initiating PrEP among the high-risk alcohol group, continuation rates remained largely uniform irrespective of alcohol use.…”
Section: Discussionmentioning
confidence: 52%
“…Two prospective studies, including one in Uganda and Kenya among serodiscordant couples, observed a decrease in PrEP adherence and continuation with hazardous alcohol use [37, 38]. In contrast, recent studies indicate that those reporting alcohol consumption often show better adherence, supported by biomarkers confirming medication compliance [39, 40]. An illustrative example comes from a South African study involving pregnant and post-partum women where 1 in 3 women reported hazardous alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed higher adherence with alcohol use and lower income; generally, in the literature, women with competing demands (e.g., lower income, alcohol use [50,51]) struggle with adherence. Perhaps in this context, women faced other challenges that encouraged them to engage in their HIV prevention strategy; this positive association with alcohol use was also observed among pregnant women accessing PrEP in Cape Town [52] and men accessing PrEP in rural KwaZulu-Natal [53], suggesting that alcohol use should not be a contra-indication to PrEP care. In a nested qualitative substudy, women in our cohort described challenges getting to study visits (including for refills), succeeded when they were able to disclose PrEP use to a supporter, and made decisions about PrEP use based on sexual activity [24].…”
Section: Discussionmentioning
confidence: 99%
“…At baseline, the participants were asked with regard to the number of sexual activity, condom use during the last sex, number of sexual partners in the past 12 months, HIV status of the partner in the past 12 months, intimate partner violence (IPV) in the past 12 months (WHO IPV scale) ( 25 ), and alcohol use in the past 12 months and before finding out about their pregnancy using the AUDIT-C ( 26 ). Alcohol use was defined as reporting any alcohol use or by a cutoff of AUDIT-C score of ≥3, which was used in our previous study to identify hazardous alcohol use among pregnant women in South Africa ( 20 ). We also reported pregnancy status at 1, 3, and 6 months and HIV risk perception and number of sex acts at 3 and 6 months.…”
Section: Methodsmentioning
confidence: 99%